2012
DOI: 10.1074/jbc.m112.383505
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Functional Interactions between Drosophila Homologue of Swc6/p18Hamlet Subunit of the SWR1/SRCAP Chromatin-remodeling Complex with the DNA Repair/Transcription Factor TFIIH

Abstract: Background: TFIIH interacts with multiple factors. Results: The fly p8 subunit of TFIIH is encoded in a bicistronic transcript with the homolog of the Swc6/p18Hamlet subunit of the SWR1/SRCAP complex and physically and genetically interacts with TFIIH. Conclusion: There is a functional link between Swc6/p18Hamlet and TFIIH. Significance: This functional interaction opens new avenues to study how TFIIH modulates transcription and DNA repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 55 publications
0
27
0
Order By: Relevance
“…We have previously reported a p8 gene null allele ( p8 − ), which is semilethal, though the males are sterile [16]. Semi-lethality and sterile organisms were also observed from heteroallelic combinations between a P-element insertion allele ( p52 EP3605 ) and point mutation alleles ( p52 mrn 3  and p52 mrn 5 ) in the p52 subunit of TFIIH [15].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously reported a p8 gene null allele ( p8 − ), which is semilethal, though the males are sterile [16]. Semi-lethality and sterile organisms were also observed from heteroallelic combinations between a P-element insertion allele ( p52 EP3605 ) and point mutation alleles ( p52 mrn 3  and p52 mrn 5 ) in the p52 subunit of TFIIH [15].…”
Section: Resultsmentioning
confidence: 99%
“…The Pc-GFP transgenic line (BL9593) was obtained from the Bloomington Stock Center. The p52 EP3605 , p52 mrn 5 , p52 mrn 3  and p8 − alleles were previously described [15,16]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it has been shown that Dmp52, the Drosophila homolog of the p52 subunit of TFIIH, interacts with Dmp18, the homolog of Swc6/p18, a subunit of the SWR1/SRCAP complex responsible for H2AZ exchange in fungi and vertebrates (84). TFIIH might also disturb histone posttranslational modifications (PTMs) that normally occur on activated promoters (85).…”
Section: Nucleotide Excision Repairmentioning
confidence: 99%
“…Lysates were clarified to 13,000 rpm at 4˚C. CoIPs were performed as indicated in Herrera-Cruz et al (Herrera-Cruz et al, 2012) Antibodies Antibodies used were Dp53: D-200 and H3 (both antibodies recognize the two Dp53 isoforms), p62 Q-19, p89 S-19 and Cdk7 ds-17 (Santa Cruz); Dp53-H3 and Anti-BrdU G3G4 (Hybridoma Bank). Dmp52 antibody was raised using a carboxy-terminal peptide (-CDVKRYWKKYSKSGV-) by New England Peptides.…”
Section: Pulldown Assaymentioning
confidence: 99%